Analisis Pemintaan dan Valuasi Ekonomi Pantai Setrojenar, Kabupaten Kebumen dengan Pendekatan Travel Cost - Maghfiroh, Alfa; Priyono, Rakhmat; Bambang, Bambang (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
Setrojenar Beach is one of the tourist attractions in Kebumen Regency, precisely in Setrojenar Village, Buluspesantren District. This beach has low quality facilities but high tourism demand. The high demand for tourism on Setrojenar Beach by the public should be accompanied by high appreciation. However, the appreciation for Setrojenar Beach is quite low as shown by the absence of an entrance ticket. So an economic valuation is needed to calculate the economic value of Setrojenar Beach, one of which is the individual travel cost method. This research has an update in terms of variables, namely the old variable knowing. The purpose of this study is to analyze the factors that influence tourist demand and determine the economic value of Setrojenar Beach. This study used 100 visitors who were taken by stratified random sampling. Data was collected using a questionnaire and distributed to respondents. The analysis technique used is multiple linear regression. This research is located at Setrojenar Beach.